Self-Efficacy in Habit Building: How General and Habit-Specific Self-Efficacy Influence Behavioral Automatization and Motivational Interference - Stojanovic, Marco; Fries, Stefan; Grund, Axel (Frontiers in Psychology, 2021)
In this paper, we investigate the role of self-efficacy in intentional habit building. We analyzed event sampling data from a habit building app we created that helps define and track habit data. We used hierarchical growth curve modeling and multilevel mediation to test our hypotheses. In a first study, N = 91 university students built new study habits over a period of 6 weeks in a controlled study. We found that the trait-like (Level 2) general self-efficacy (GSE) predicted automaticity (i.e. habit strength) but not the experience of motivational interference (MI). In a second study with real user data, N = 265 idiographic habits have been analyzed. The specific self-efficacy associated with these habits - habit-specific self-efficacy (Level 1, HSE) - was measured during habit formation. We found that lagged HSE predicted automaticity and that lagged automaticity predicted HSE, indicating a positive feedback mechanism in habit building. Furthermore, we found that lagged HSE predicted less MI during habit performance. A multilevel mediation analysis showed significant effects of lagged HSE (Level 1) and aggregated HSE (Level 2) on MI, which were both partially mediated by automaticity. These results show the importance of defining the specificity of self-efficacy beliefs and how they interact with automaticity in the habit building process. Keywords: Habit formation, specific self-efficacy, general self-efficacy, motivational interference, self-regulation, automaticity, app intervention